ANALISIS PENDAPATAN USAHATANI PADI SAWAH DI KELURAHAN SISIPAN KECAMATAN BATUI KABUPATEN BANGGAI - Ladonu, Moh Ilham; Madaa, Syamsul Bahri; A Zaenuddin, Ruslan; Rustiawati, Yuni; Djamaluddin, Ismail (Fakultas Pertanian Universitas Tompotika Luwuk, 2024)
The increase in production of a farm is an indicator of the success of the farm concerned, however, the high production of a commodity obtained per unit of land area does not guarantee the high income of paddy rice farming which is influenced by the price received by farmers and the costs of using farm inputs. The purpose of this study was to determine the income and feasibility of Rice Paddy Farming in Sisipan Village, Batui District, Banggai Regency. This research was conducted in June-August 2024 in Sisipan Village, Batui District. The analysis method used in this research is income analysis, and feasibility analysis. The results showed that the results of paddy rice farming in Sisipan Village, Batui Subdistrict benefited farmers by obtaining an average income of Rp.37,835,190.48 / growing season and paddy rice farming in Sisipan Village, Batui Subdistrict Feasible as a business with a value> 1 or a = 7.42.